Inherited Thrombophilia and First Venous Thromboembolism during Pregnancy and Puerperium - Martinelli, Ida; De Stefano, Valerio; Taioli, Emanuela; Paciaroni, Katia; Rossi, Elena; Pier, Mannucci Mannuccio (Thrombosis and Haemostasis, 2002)
Venous thromboembolism is a rare but threatening complication of pregnancy. Little conclusive information is available on the actual risk of venous thromboembolism during pregnancy or puerperium in women with inherited thrombophilia, particularly in carriers of factor V Leiden and of the G20210A prothrombin gene mutation. To determine the pregnancy-related and puerperium-related risk of venous thromboembolism in women with inherited thrombophilia, we performed a case-control study on 119 women who had a first episode of deep vein thrombosis and/or pulmonary embolism during pregnancy or puerperium and 232 healthy women who had at least one pregnancy without thrombosis. Inherited thrombophilia was diagnosed in 47 patients (39.5%) and 15 controls (6.5%). The relative risk of venous thromboembolism was 10.6 (95% CI, 5.6-20.4) for heterozygous carriers of factor V Leiden, 2.9 (95% CI, 1.0-8.6) for heterozygous carriers of the prothrombin mutation and 13.1 (95% CI, 5.0-34.2) for those with antithrombin, protein C or protein S deficiency taken together. Sixty-eight of the 119 women (57%) had thrombosis after delivery, confirming the puerperium as a particularly high-risk period. When women were divided into two groups of those with antenatal or postnatal thrombosis, the relative risks associated with each type of inherited thrombophilia were of similar magnitude. In conclusion, women with inherited thrombophilia have an increased risk of venous thromboembolism during pregnancy. Among thrombophilic abnormalities, the prothrombin mutation was the weakest risk factor. Thrombosis occurred more frequently in puerperium than in pregnancy, whether or not thrombophilia was diagnosed.
Keywords: Blood coagulation; factor V Leiden; prothrombin mutation; risk factors